Impact of Mobile Phones on Staple Food Markets in Mozambique: Improved Arbitrage or Increased Rent Extraction? - Wouter Zant (Tinbergen Institute, 2017)
I use the quasi experimental nature of the roll-out of the mobile phone network in Mozambique to estimate the impact of search costs on the dispersion of maize prices and transport costs. The introduction of mobile phone services from 1997 to 2009 explains a 4.5-11% percent reduction in price dispersion of maize prices, and a slightly larger reduction in per ton km transport costs. Apart from an improvement of the efficiency of maize markets, the evidence suggests that traders benefit by capturing increased rent income. Various sources of potential heterogeneity are identified: the reduction is larger for pairs connecting remote locations, for source markets with a low poverty head count and with a higher mobile phone coverage in neighbouring markets, and during drought periods.
Keywords: O13; O33; Q11; Q13; 330; search costs; transport costs; mobile phones; agricultural markets; maize prices; sub-Saharan Africa; Mozambique